Improving patient tolerability in immunoglobulin treatment: focus on stabilizer effects. (June 2013) - Sun, Adam; Teschner, Wolfgang; Yel, Leman
Various types of excipients are added to immunoglobulin preparations to stabilize the product and prevent aggregation and dimer formation. These excipients, which are also called stabilizers or additives, are not inert chemicals and may have clinical implications. This is one reason why immunoglobulin products are not interchangeable. Herein, immunoglobulin preparation, excipient types and the differences among sugar stabilizers and the amino acids, glycine and proline as excipients, are presented. Preclinical studies that unravel the complexities of dimer reduction are summarized. Details of patient considerations with respect to excipient content are outlined focusing on patients with renal insufficiency, diabetes, corn allergy, hereditary fructose intolerance, inborn errors of proline metabolism, DiGeorge Syndrome and neuropsychiatric disorders associated with hyperprolinemia. Excipients are essential components of immunoglobulin preparations and their presence should be a consideration when matching patient needs to product characteristics.